PWE-069 Differences in luminal distribution and clinical characteristics of ulcerative colitis in south asians and white british in the north of england. (22nd June 2015) - Khan, MA; Newman, W; Hill, J
Abstract : Introduction: Inflammatory bowel diseases (IBD) are inflammatory conditions that affect the gastrointestinal tract and may have extra intestinal manifestations. The two main subtypes are Crohn's disease (CD) and ulcerative colitis (UC). The incidence of IBD has traditionally been higher in Caucasian populations in Europe, North America and Australia compared to other regions of the world. There is now evidence of increasing incidence in all populations worldwide. Studies from the UK, North America, Malaysia and Singapore have observed a 2–3 times higher incidence of IBD in South Asian immigrant populations compared to local cohorts. However, few studies have described the disease phenotype and mucosal distribution in the South Asian immigrant population. Method: Ethics approval was obtained ref: O5/Q1407/274. Patients were recruited prospectively in 11 centres in the North Of England. Inclusion criteria were diagnosis of UC and age >16 years. Exclusion criteria were Diagnosis of IBDU or IDC and Age <16 years. Information was collected on a standard clinical proforma. Data was stored on a FileMaker Pro database. Chi Squared analysis was used to compare groups. Results: In total 186 South Asians (SA) and 535 White British (WB). In the South Asian cohort males were more likely to be affected compared to White British. South Asians had a younger average age of diagnosis 30 vs. 40 for White British. There were differences in luminal distribution with South Asians more likely to have Extensive Colitis (45% vs. 26%) or Left sided colitis (42% vs. 22%) and White British more likely to have Proctitis (13% vs. 52%). The differences in luminal distribution between groups were highly statistically significant. There was no statistical difference in family history between groups with 21% of South Asians vs. 27% for White British. There was also no statistical difference in need for colectomy between groups (5% for SA vs. 3% for White British). Also there was no statistical difference in the presence of EIM's 6% for SA vs. 5% for White British. Conclusion: There are significant differences in luminal distribution and age of diagnosis between groups. South Asians had a younger age of onset and more extensive colitis, but the relatively low rate of colectomy and EIM's which suggest a less severe disease phenotype. In addition the younger age of onset and extensive disease in South Asians may influence risk of colorectal cancer in the future. These differences may represent differences in disease pathogenesis in particular genetic susceptibility or environmental factors. This information will help inform current and future genotype studies. Disclosure of interest: None Declared.